Rigorous network modeling of magnetic-resonant wireless power transfer. Issue 1 (March 2014) - Costanzo, Alessandra; Dionigi, Marco; Mastri, Franco; Mongiardo, Mauro; Russer, Johannes A.; Russer, Peter
<x content-type="archive" xml:space="preserve">Abstract</x> Magnetic-resonant wireless power transfer (MRWPT) has been typically realized by using systems of coupled resonators. In this paper, we introduce a rigorous network modeling of the wireless channel and we introduce several viable alternatives for achieving efficient MRWPT. Ideally, the wireless channel should realize a 1:n transformer; we implement such transformer by using immittance inverters. Examples illustrate the proposed network modeling of the magnetic-resonant wireless power channel.